Manfaat Studi Biblika Kontekstual dalam Membangun Ajaran Ekoteologis di Masa Pasca Pandemi Covid-19 - Restifani Cahyami (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2023)
Ecology is a serious problem, especially during the Covid-19 pandemic. Therefore it is not surprising that various theological understandings related to pandemic ecology have emerged which have influenced the understanding of Christians. Facing the various onslaughts of ecological theology in the post-pandemic period, this paper is intended to provide an explanation regarding the benefits and importance of involving contextual biblical studies in building teachings in the post-Covid-19 pandemic period related to ecotheology. The method used in this study is a qualitative method with data sources from literature review and simple observations in the field. The goal is that the theology that is built produces teachings that are in accordance with the Bible as the main source of theology. The results show that contextual biblical studies are very useful in building teachings that are based on the Bible specifically in responding to current problems regarding ecotheology. This is because contextual biblical theology does not only answer the context but uses and involves the text within it. However, far from that the result of the interpretation that is built is not only understood as a teaching but goes beyond that, namely living the interpretation by loving nature as part of God's creation.